Cortical bone-derived stem cell therapy reduces apoptosis after myocardial infarction - Hobby, Alexander R. H. (Am J Physiol Heart Circ Physiol, 2019)
Ischemic heart diseases such as myocardial infarction (MI) are the largest contributors to cardiovascular disease worldwide. The resulting cardiac cell death impairs function of the heart and can lead to heart failure and death. Reperfusion of the ischemic tissue is necessary but causes damage to the surrounding tissue by reperfusion injury. Cortical bone stem cells (CBSCs) have been shown to increase pump function and decrease scar size in a large animal swine model of MI. To investigate the potential mechanism for these changes, we hypothesized that CBSCs were altering cardiac cell death after reperfusion. To test this, we performed TUNEL staining for apoptosis and antibody-based immunohistochemistry on tissue from Göttingen miniswine that underwent 90 min of lateral anterior descending coronary artery ischemia followed by 3 or 7 days of reperfusion to assess changes in cardiomyocyte and noncardiomyocyte cell death. Our findings indicate that although myocyte apoptosis is present 3 days after ischemia and is lower in CBSC-treated animals, myocyte apoptosis accounts for <2% of all apoptosis in the reperfused heart. In addition, nonmyocyte apoptosis trends toward decreased in CBSC-treated hearts, and although CBSCs increase macrophage and T-cell populations in the infarct region, the occurrence of apoptosis in CD45(+) cells in the myocardium is not different between groups. From these data, we conclude that CBSCs may be influencing cardiomyocyte and noncardiomyocyte cell death and immune cell recruitment dynamics in the heart after MI, and these changes may account for some of the beneficial effects conferred by CBSC treatment. NEW & NOTEWORTHY The following research explores aspects of cell death and inflammation that have not been previously studied in a large animal model. In addition, apoptosis and cell death have not been studied in the context of cell therapy and myocardial infarction. In this article, we describe interactions between cell therapy and inflammation and the potential implications for cardiac wound healing. Listen to this article's corresponding podcast at https://ajpheart.podbean.com/e/cortical-bone-derived-stem-cell-therapy-reduces-apoptosis/.